Towards a Circular Economy in Jordan: Selecting Organic Waste Treatment Options Using a Multi-Criteria Decision-Making Approach - Abu-Qdais, Hani; Al-Omoush, Sarah; Jalalipour, Haniyeh; Nassour, Abdallah (Sustainability, 2025)
Solid waste management in Jordan is still following a linear model, where more than 90% of solid waste, including organic waste, is collected and disposed into landfills. Such practices are not sustainable and may lead to adverse public health and environmental impacts. Therefore, there is a pressing need to look for alternative organic waste management by adopting circular economy principles through which the adverse impacts are minimized and the benefits from the resources are maximized. The main objective of this study is to select the appropriate treatment technology for organic solid waste management in Jordan. To achieve this objective, an analytical hierarchy process was used as a decision making tool. A hierarchy model that consists of four levels was employed with 3 main criteria and 10 sub-criteria to assess 4 alternatives of organic waste treatment. Based on the experts’ opinions and the pairwise comparison, the AHP model results showed that the environmental and public health criterion is the most important. On the other hand, the most sustainable treatment option of the organic waste treatment is composting with a weight of 0.373, followed by landfilling with a weight of 0.203. Anaerobic digestion ranked third as an alternative, with a weight of 0.201, while the least-preferred treatment technology was found to be the mechanical biological treatment, with a weight of 0.193. Sensitivity analysis based on varying the main criteria weights under different scenarios showed the robustness of the AHP model, where composting continued to be the first ranked under most of the considered scenarios. Since the national solid waste management strategy is currently subject to review, the findings of the current study provide a valuable information for the decision makers in Jordan to update their strategic plans and move towards a circular economy option.